2017
DOI: 10.1103/physrevb.96.085110
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz diffraction enhanced transparency probed in the near field

Abstract: Electromagnetically induced transparency in metamaterials allows to engineer structures which transmit narrow spectral ranges of radiation while exhibiting a large group index. Implementation of this phenomenon frequently calls for strong near-field coupling of bright (dipolar) resonances to dark (multipolar) resonances in the metamolecules comprising the metamaterials. The sharpness and contrast of the resulting transparency windows thus depends strongly on how closely these metamolecules can be placed to one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…In this article, we experimentally study the coupling of the Fano resonance of an asymmetric split ring resonator (ASRR) to the FOLM of the resonator array. Previous studies have shown enhanced Q factors by coupling a lattice mode to inductive–capacitive (LC) resonances and electromagnetically induced transparency‐type (EIT‐type) resonances. Here, we demonstrate FOLM coupling to a Fano resonance obtained through magnetic coupling and observe both Q factor and FoM enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, we experimentally study the coupling of the Fano resonance of an asymmetric split ring resonator (ASRR) to the FOLM of the resonator array. Previous studies have shown enhanced Q factors by coupling a lattice mode to inductive–capacitive (LC) resonances and electromagnetically induced transparency‐type (EIT‐type) resonances. Here, we demonstrate FOLM coupling to a Fano resonance obtained through magnetic coupling and observe both Q factor and FoM enhancement.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, there are no fundamental works describing how to achieve robust BICs on a general basis, except for well-known symmetry-protected and accidental degeneracies appearing in photonic crystals [3] and asymmetric metasurfaces [7]. A variety of resonant phenomena, such as surface plasmon lattice resonances in the optical domain [13][14][15][16][17][18][19], Fano resonances [20][21][22][23][24][25][26], and electromagnetically induced transparency at optical and THz frequencies [27][28][29][30][31][32][33][34][35][36], have been reported in metasurfaces; however, robust symmetry-protected BICs remain unexplored. Metasurfaces are especially interesting for this purpose due to their enhanced collective response [21,26,[37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, recall the classical analogue of quantum electromagnetically‐induced transparency (EIT) has been widely explored in metasurfaces, where the three level system needed is typically replaced by mode coupling of two resonances of various kinds. [ 34–45 ] Nonetheless, even though, as mentioned above for BICs in general, metasurface quasi‐BICs with high Q‐factors have been widely investigated, [ 5,13,18,46–48 ] the use of BICs to achieve ultra‐narrow EIT has not been explored thus far.…”
Section: Introductionmentioning
confidence: 99%